Answer:
1.2
Step-by-step explanation:
First make -1.5 equal to 0.
We'll have to add 1.5, right?
So 1.5 is in 2.7.
So now its 0 + ? = ?
2.7 - 1.5 = 1.2
So 0 + 1.2 = 1.2
Hope this helped.
Answer:
a
Step-by-step explanation:
if you plug 4 in for x it solves it
Hi there!
»»————- ★ ————-««
I believe your answer is:
(-3, -1) and (1, 3)
»»————- ★ ————-««
Here’s why:
- I have graphed the two equations given on a graphing program.
- When graphed, they pass at points (-3, -1) and (1,3). Therefore, they are the solutions to the system.
⸻⸻⸻⸻
See the graph attached.
⸻⸻⸻⸻
»»————- ★ ————-««
Hope this helps you. I apologize if it’s incorrect.
Answer:
50
Step-by-step explanation:
since the Pythagorean theorem is
√![a^2+b^2](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2)
b is the bottom line (48)
a is the right line (14)
c is the top line (c)
plug that in
√![14^2 + 48^2](https://tex.z-dn.net/?f=14%5E2%20%2B%2048%5E2)
then do the exponets
= 14 * 14 = 196
= 48 * 48 = 2304
then add them together
196 + 2304 = 2500
√2500
the sqrt of 2500 is 50 (50 * 50 = 2500)
c = 50
your answer is 50
hope this helps:)